Effect of pressure on corrosion behavior of X60, X65, X70, and X80 carbon steels in water-unsaturated supercritical CO2 environments. (August 2016) - Xu, Minghe; Li, Weihong; Zhou, Yi; Yang, XiaoXian; Wang, Zhe; Li, Zheng
Graphical abstract: Highlights: Effect of pressure and water content on corrosion behavior in SC-CO2 . Corrosion behavior of X60, X65, X70, and X80 steel is compared. More serious general and localized corrosion at 8 MPa with H2 O content of <2600 ppm. More serious general and localized corrosion at 10 MPa with H2 O content of 3000 ppm. Safe limit of water content is 1600 ppm at 10 MPa and less than 1600 ppm at 8 MPa. Abstract: A systematic study was performed to investigate the effect of pressure and water content on the general corrosion and localized attack of carbon steels during the transport of CO2 for the CCS industry. Corrosion experiments were conducted on X60, X65, X70, and X80 carbon steels in water-unsaturated supercritical CO2 with SO2 and O2 in conditions of 50 °C and 8–12 MPa. The general corrosion rates increased with water content and ranged from 0.02 mm/year to 0.31 mm/year at 8 MPa and from 0.01 mm/year to 0.94 mm/year at 10 MPa. Localized corrosion was determined by measuring the penetration rate and pitting factor. The penetration rates ranged from 0.2 mm/year to 3.25 mm/year at 8 MPa and from 0.04 mm/year to 6.02 mm/year at 10 MPa. Meanwhile, the pitting factors ranged from 4 to 70 at 8 MPa and from 3 to 43 at 10 MPa, with water contents varying from 1600 ppm to 3000 ppm. The degrees of general corrosion and localized attack were higher at 8 MPa than those at 10 MPa, with water contents ranging from 1600 ppm to 2600 ppm, but lower at a water content of 3000 ppm.